Children of the wolf : a novel - Yolen, Jane. (New York, N.Y., U.S.A. : Puffin Books, 1993)
In 1920 in India two children that have been raised by wolves are discovered and brought to an orphanage to be taught human behavior again.
"Ages 12 up"--Cover.
Elem. School Library Collection.
Horn Book.
Wilson's Junior High School.
7-9
Young Adult
Keywords: Feral children -- Fiction; Feral children -- Fiction; India -- Fiction; India -- Fiction